Dynamic response analysis of wind turbines under blade pitch system fault, grid loss, and shutdown events. (13th June 2013) - Jiang, Zhiyu; Karimirad, Madjid; Moan, Torgeir
ABSTRACT This study focuses on the dynamic responses of land‐based and floating wind turbines under blade pitch system fault and emergency shutdown conditions. The NREL 5 MW turbine is studied. A hydraulic pitch system is considered, and the faults under study are events with a seized blade or a blade running out of control. Emergency shutdown is defined as a fast pitch‐to‐feather maneuver of the blades. Load cases with power production and grid fault with ensuing shutdown are also analysed for comparison. The fault scenarios and the blades' fast pitching activity are simulated using HAWC2 through external Dynamic Link Libraries. On the basis of the time‐domain simulations, the response characteristics of the land‐based and the floating turbines in the four design load cases are compared. The load effects from the fault conditions are compared with the operational cases. Strong system dynamics and resonant responses, such as the tower elastic mode and the yaw resonant response, are elicited during shutdown. If the pitch system has a fault and one blade is hindered from normal pitching, the uneven load distribution of the blades leads to large structural and motion responses. For both turbines, the response maxima vary cyclically with the instantaneous azimuth when the blades start pitching to feather. For the floating wind turbine, the interaction of waves and wind also affects the results. The effect of the pitch rate during shutdown is analysed. The responses of the land‐based turbine in grid loss and shutdown conditions are proportional to the pitch rate, whereas decreased sensitivity is found in the cases with pitch system faults. For the floating turbine, the effect of the pitch rate is small, and reduced pitch and yaw motion extremes are observed as the pitch rate increases. Copyright © 2013 John Wiley & Sons, Ltd.